INTEGRATIVE BEHAVIORAL COUPLE THERAPY: OVERVIEW OF A MODEL WITH EMPHASIS ON EMOTIONAL ACCEPTANCE - Vargas Madriz, Luis Francisco (2013)
This article reviews the Integrative Behavioral Couple Therapy (IBCT), which is a clinical intervention model that emphasizes in the acceptance of the differences between members of the couple, allowing them to grow closer in those differences. The article states the theoretical foundations of the therapy, its formulations for the session structure, its interventions strategies and the clinical skills required in the therapists. It finalizes with a critical analysis of the employment of IBCT in Costa Rica.